THERMODYNAMICS OF SOME PHYSICAL AND CHEMICAL TRANSFORMATIONS IN POLYPHASE CERAMIC MATERIALS - M.Kulbek; D.Baimolda; E.Dzhaksigeldinova; G.Zhexenbayeva; N.Aytan (Academics and Science Reviews Materials, 2023)
When firing polyphase ceramic materials in certain temperature ranges, phase and chemical transformations of various nature occur. A significant part of these transformations proceed with the absorption or release of a certain amount of heat, i.e. accompanied by thermal effects. The scientific article outlines some issues of thermodynamics of first-order phase transformations that take place in these materials. In particular, methods are shown for determining the total amount of heat, as well as the specific heat of phase transformations associated with dehydration and dissociation in polyphase ceramic materials. Examples of the practical use of the proposed calculation methods are given. The computational work was carried out at laboratory of applied thermophysics and new technologies of KazNPU named after Abai, using experimental data obtained on polyphase monothermitic model samples. In this case, the specific heat of phase transformations (dehydration) were determined in two ways, where the results showed good convergence.